An Analysis of the Convergence Level of Tangible Assets (PPE) According to Romanian National Accounting Regulation and IFRS for Smes - Maria Madalina Buculescu (Costica); Bogdan Nicolae Velicescu (Journal of Accounting and Management Information Systems (JAMIS), 2014)
This paper aims a comparative analysis between IFRS for SMEs and Romanian national accounting regulations concerning measurement of formal convergence level of definitions, treatment and policies of Property, Plant and Equipment (PPE) and highlighting main national fiscal rules related. With the purpose to not contribute only to the measurement of PPE formal level of harmonization, we intend to analyze some PPE related accounting practices used by Romanian certified accountants. To this effect we addressed an on-line questionnaire to certified accountants including questions concerning their opinion to: fair value method used for revaluation, accelerated depreciation, the limit value for tangible assets and inventory objects. Finally, we assessed a medium level of formal convergence in the area of PPE, but there are significant impediments if the case of a possible implementation of IFRS for SMEs especially because of the fiscal rules which usually influence accounting practices and because professional accountants considerably agree PPE practices which are not common within IFRS for SMEs.
Keywords: M41; 650; tangible assets (PPE); accounting convergence/harmonization; fiscal rules; OMFP 3055/2009; International Financial Reporting Standard for Small and Medium sized Enterprises (IFRS for SMEs)